A Novel High Gain SEPIC Converter with the Tapped Inductor Model Operating in Discontinuous Conduction Mode for Power Factor Correction - Sathiyamoorthy S; Gopinath M (Institute of Advanced Engineering and Science, 2016)
Power Factor Correction (PFC) has become one of the most active research areas in the field of power electronics due to the surplus power required for various industrial applications around the world. In this work, a novel SEPIC converter with the Tapped Inductor model operating in Discontinuous Conduction Mode (TI-SEPIC- DCM) is proposed for PFC. The proposed TI-SEPIC-DCM improves the voltage gain through voltage multiplier cell and charge pump circuit. The voltage multiplier cell also helps in attaining the Zero-Voltage Switching (ZVS) and Zero-Current Switching (ZCS), which results in higher switching frequency and size reduction. Moreover, a third order harmonic reduction control loop has been proposed for better harmonic mitigation. The proposed work has been simulated in MATLAB and the results are obtained to validate the significance of the proposed TI-SEPIC- DCM with near unity power factor and reduced harmonics.